The sociology book - Thorpe, Christopher; Yuill, Chris; Hobbs, Mitchell; Todd, Megan; Tomley, Sarah; Weeks, Marcus (2015)
Profiles the world's most renowned sociologists and more than 100 of their biggest ideas, including issues of equality, diversity, identity, and human rights; the effects of globalization; the role of institutions; and the rise of urban living in modern society.
Includes index.
Keywords: Sociology; Sociology; Sociology